Allogeneic transplantation in lymphoma: current status - Norbert Schmitz; Peter Dreger; Bertram Glass; Anna Sureda (Haematologica, 2007)
Allogeneic transplantation of hematopoietic stem cells (allo-SCT) is being increasingly used to treat patients with lymphoma. We describe current results of allo-SCT in patients with Hodgkin’s disease, indolent lymphoma including Waldenström’s disease, and aggressive lymphoma including mantle cell lymphoma and mature T-cell lymphomas. A Graft-vs.-Lymphoma (GvL) effect is present in most entities as evidenced by the generally lower relapse rates after allo-SCT and the results of donor lymphocyte infusions. Slowly proliferating diseases like chronic lymphocytic leukemia, indolent lymphomas, and some T-cell lymphomas are particularly sensitive to the effects of allogeneic T-cells while patients with Hodgkin’s disease and aggressive lymphoma may need vigorous debulking before allo-SCT to achieve optimal results. Although reduced-intensity conditioning has lowered transplant-related mortality in most and improved survival in some sub-entities, relapse rates in patients with Hodgkin’s disease and aggressive B-cell lymphomas, as well as in patients with heavily pre-treated and refractory lymphoma, remain high and further improvement is undoubtedly needed. Large prospective studies in well-defined entities are necessary to further clarify the role of allo-SCT in lymphoma.